2002
DOI: 10.1108/13632540210807099
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of relationships between communication style and leader‐member exchange

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 43 publications
(47 reference statements)
2
45
0
1
Order By: Relevance
“…We are aware of only one study exploring LMX and feedback (Kramer, 1995), and it does not address both perspectives of the exchange. There have been more studies examining the role of communication within LMX relationships, such as studies of LMX and communication frequency (Kacmar et al, 2003), communication style (Yrle, Hartman, & Galle, 2002), gender-based differences in communications (Fairhurst, 1993), and social structure (Fairhurst & Chandler, 1989). Future research exploring both the quantity and quality of feedback and its effects on LMX congruence seems merited.…”
Section: Relational Dynamicsmentioning
confidence: 95%
“…We are aware of only one study exploring LMX and feedback (Kramer, 1995), and it does not address both perspectives of the exchange. There have been more studies examining the role of communication within LMX relationships, such as studies of LMX and communication frequency (Kacmar et al, 2003), communication style (Yrle, Hartman, & Galle, 2002), gender-based differences in communications (Fairhurst, 1993), and social structure (Fairhurst & Chandler, 1989). Future research exploring both the quantity and quality of feedback and its effects on LMX congruence seems merited.…”
Section: Relational Dynamicsmentioning
confidence: 95%
“…An obvious reason why LMX differentiation may affect employee reactions is because of the relative advantage afforded to individuals in high quality LMX relationships, but not to individuals in low quality LMX relationships. By definition, high quality LMX relationships involve more tangible and intangible resources being exchanged within the leader-employee dyad, for example: respect, trust, obligation (Graen & Uhl-Bien, 1995), affect, loyalty, professional respect (Dinesch & Liden, 1986;Liden & Maslyn, 1998), information, influence, support (Dansereau et al, 1975), voice (Yrle, Hartman & Galle, 2002), positive performance appraisals (Duarte, Goodson & Klich, 1993, 1994, and career progress (Wakabayasi, Graen, Graen & Graen, 1988). Several authors have suggested that such inequalities in reward distribution may negatively affect relations among team members (e.g., Graen & Uhl-Bien, 1995;Liden, Sparrowe & Wayne, 1997;Sias & Jablin, 1995); however, few empirical studies have examined the impact of LMX differentiation on employee reactions.…”
mentioning
confidence: 99%
“…In traditional dyadic relationships, the supervisor could utilize different communication behaviour with different subordinates, depending on the nature of the relationship (Dansereau & Markham, 1987;Hersey & Blanchard, 1993). Supervisor-subordinate communication requires the best possible communication traits, behaviors, strategies and styles (Yrle, Hartman, & Galle, 2002).…”
Section: Supervisor-subordinate Communication and Leadershipmentioning
confidence: 99%